Additional detail in aggregate integrated land-use models via simulating developer pro forma thinking - Johnson, Jerry; Frkonja, Jeff; Todd, Maribeth; Yee, Dennis (Journal of Transport and Land Use, 2018)
This paper describes an enhancement to MetroScope, the land-use model component of an integrated model suite used to answer current- and next-generation policy questions facing Oregon Metro (the Portland regional planning organization) and other public agencies. The enhancement is designed to simulate more-detailed housing developer decision processes within an overall aggregate spatial equilibrium model (SEM) framework via a pro forma paradigm. The paper enumerates the policy questions that motivated the enhancement, discusses the integrated model framework, briefly reviews levels of detail available in existing models as context, and frames potential future research directions for additional decision process detail that would be helpful in the consumer modules of the model and potentially other SEMs currently in use.